(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Environment plays crucial role in sustenance of ecosystems on earth. Changes in environment are impacting the ecosystem. Biotic and abiotic components of ecosystem are getting severally affected by undesirable changes in environment. Ecology, diversity and sustainability of ecosystem are getting affected by changes in environment. Degradation in various environmental components factors including air, water, soil and changes in various climatic factors including rainfall pattern, temperature has resulted in air pollution, water pollution, soil pollution and global warming, eventually leading to imbalances in ecosystems. Aquatic ecosystems are prone to water pollution while many fragile ecosystems are prone to climate change. Ecological consequences of degradation in environment are affecting the relationship between living organism and environment.